Pengaruh Faktor Tekanan, Peluang, Rasionalisasi, Kompetensi, dan Arogansi Terhadap Kecurangan Laporan Keuangan - Dian Fathma Alfina; Amrizal Amrizal (Akuntabilitas, 2020)
This study was to examine the influences of the fraud pentagon theory’s factors towards the financial statement fraud on banking listed in BEI for the period of 2014-2018. This study consisted of nine independent variables. Four variables of pressure (financial stability, external pressure, financial targets, personal financial needs). Two variables of the opportunity (nature of industry, ineffectiveness of monitoring). And a variable of rationalization, competence, and arrogance. Based on the results of Beneish M-Model analysis, out of 43 banks, 28 of them were indicated to have manipulated their financial statements during the study period. Meanwhile, the results of logistic regression analysis showed a positive influence of financial stability (ACHANGE), personal financial needs (OSHIP), nature of the industry (RECEIVABLE), ineffective monitoring (IND), competence (DIRCHANGE), and arrogance (CEOPIC) on financial statement fraud, while external pressures (LEV), financial targets (ROA), and rationalization (AUDCHANGE) have a negative effect on financial statement fraud